OVERVIEW OF THE PHILOSOPHY OF MATHEMATICS: DESCRIPTION OF THE DIALOGUE METHOD OF SOCRATES AND PAULO FREIRE AND ITS IMPLICATIONS IN MATHEMATICS LEARNING - Maysun, Maysun; Hakim, Lukman El; Aziz, Tian Abdul (Nindikayla Institute, 2023)
Mathematics has an important role for improving attitudes and behavior through critical thinking. The learning method that can be applied to improve critical thinking skills is the dialogue method. Dialogue activities will provoke students to be more active in learning and educators can gather information, generate responses, focus students' attention, and test students' understanding. Socrates and Paulo Freire are two important figures who apply the dialogue method in learning. This research aims to describe the philosophical review of Socrates' dialogues and Paulo Freire's dialogues and their implementation in learning mathematics. The research method used is qualitative with library research. The result of this study is that the researcher found that the dialogue method can create an interesting and interactive classroom atmosphere. Through the dialogue process, educators can facilitate students to hone and improve their critical thinking skills